2023
DOI: 10.22159/ijpps.2023v15i3.47008
|View full text |Cite
|
Sign up to set email alerts
|

2d-Qsar Study on Some Novel Dihydropyrimidine-4-Carbonitrile Analogs as an Antifungal Activity

Abstract: Objective: The present study was designed to study the antifungal activity of Dihydropyrimidine-4-Carbonitrile analogs against the fungi Candida albicans by a 2D quantitative structure-activity relationship (QSAR) model. Methods: The pyrimidine derivatives were produced using lipophilic, electronic, and steric parameters by Quantitative Structure Activity-Relationships (QSAR). A relationship between dependent and independent variables (biological activities and physicochemical descriptors, respectively) was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 25 publications
0
8
1
2
Order By: Relevance
“…Candida albicans nevertheless displayed resistance to these extracts. Aspergillus flavus, Aspergillus fumigates, Aspergillus niger, Cryptococcus neoformans, and Candida albicans all showed similar responses to Moringa leaf extract [98,99] .…”
Section: Antimicrobial Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Candida albicans nevertheless displayed resistance to these extracts. Aspergillus flavus, Aspergillus fumigates, Aspergillus niger, Cryptococcus neoformans, and Candida albicans all showed similar responses to Moringa leaf extract [98,99] .…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…The healing properties of this plant, also known as "Mother's best friend," "the miracle tree," "the horseradish tree," and "the drumstick tree," have made it a blessing to mankind. The Moringa plant is widely available, affordable, very nourishing, and well-known for its therapeutic properties [2,3] . Moringa leaves include a wide variety of macronutrients and micronutrients that are essential to both people and other living things.…”
Section: Introductionmentioning
confidence: 99%
“…Water for injection (aqua ad iniectabilia) represents the highest quality of pharmacopeial WPU 6. As it is pyrogen‐free 7, it serves for the manufacturing of drugs for parenteral use whose solvent is water 2.…”
Section: Introductionmentioning
confidence: 99%
“…The use of herbs for their therapeutic benefits is known as herbal medicine, sometimes known as herbalism or botanical medicine [ 6 ]. Numerous studies have shown that certain plants contain various compounds, such as peptides, aldehydes, alkaloids, phenols, saponins, polysaccharides, terpenoids, steroids, flavonoids and tannins, which may have critical restorative effects against bacteria, fungi, or viruses [ 7 , 8 , 9 , 10 ]. Herbal plants produce and contain a variety of chemical substances that have an impact on humans.…”
Section: Introductionmentioning
confidence: 99%